2005
DOI: 10.1136/jcp.2003.009506
|View full text |Cite
|
Sign up to set email alerts
|

The links between axin and carcinogenesis

Abstract: The products of the two mammalian Axin genes (Axin1 and its homologue Axin2) are essential for the degradation of β catenin, a component of Wnt signalling that is frequently dysregulated in cancer cells. Axin is a multidomain scaffold protein that has many functions in biological signalling pathways. Overexpression of axin results in axis duplication in mouse embryos. Wnt signalling activity determines dorsal–ventral axis formation in vertebrates, implicating axin as a negative regulator of this signalling pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
212
0
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(223 citation statements)
references
References 135 publications
3
212
0
8
Order By: Relevance
“…It has been reported that several post-translational modifications, such as phosphorylation/dephosphorylation by GSK3b/protein phosphatase1 Luo et al, 2007), SUMOlyation by SUMO-1 (small ubiquitin-related modifier) conjugating enzymes 3 (Rui et al, 2002;Kim et al, 2008), PARsylation by tankyrases (Huang et al, 2009) and ubiquitination, are involved in controlling the stability of Axin. Although it is not yet known how these modifications are related and why so many are required, cells seem to have various checkpoints that regulate the Axin concentration as Axin is a rate-limiting factor of Wnt/b-catenin signaling and is linked to other signaling pathways such transforming growth factor b and apoptosis signaling (Luo and Lin, 2004;Salahshor and Woodgett, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that several post-translational modifications, such as phosphorylation/dephosphorylation by GSK3b/protein phosphatase1 Luo et al, 2007), SUMOlyation by SUMO-1 (small ubiquitin-related modifier) conjugating enzymes 3 (Rui et al, 2002;Kim et al, 2008), PARsylation by tankyrases (Huang et al, 2009) and ubiquitination, are involved in controlling the stability of Axin. Although it is not yet known how these modifications are related and why so many are required, cells seem to have various checkpoints that regulate the Axin concentration as Axin is a rate-limiting factor of Wnt/b-catenin signaling and is linked to other signaling pathways such transforming growth factor b and apoptosis signaling (Luo and Lin, 2004;Salahshor and Woodgett, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Axin is a key scaffold protein for the b-catenin destruction complex, and mutation of Axin leads to various cancers (Salahshor and Woodgett, 2005). The presence of mutated Axin in human colorectal cancer and hepatocellular carcinomas suggest that Axin is a tumor suppressor gene as well as a potential therapeutic target molecule for various types of cancer (Satoh et al, 2000;Shimizu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For example, b-catenin can be degraded by Jade-1 (Chitalia et al, 2008), Siah-1 or other ubiquitin ligases (Dimitrova et al, 2010). Therefore, although the major mechanism of regulation of b-catenin activity is phosphorylation, the Wnt pathway may use multiple ways to regulate the concentration of b-catenin (Tolwinski and Wieschaus, 2004;Salahshor and Woodgett, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in Axin genes are more rare, and their role in tumorigenesis is less clear. Most of the described Axin1 mutations are inactivating and many are biallelic, consistent with its tumor suppressor role (Salahshor and Woodgett, 2005). Axin1 is a multidomain scaffold protein implicated in various signaling pathways, including the Wnt, JNK, transforming growth factor (TGF)b and p53 pathways (Rui et al, 2004;Salahshor and Woodgett, 2005).…”
mentioning
confidence: 95%
“…Axin1 has also been implicated in several other signaling pathways (Rui et al, 2004;Salahshor and Woodgett, 2005). Axin1 is a master scaffolding protein that can be a negative regulator of the Wnt pathway, but a positive regulator of the JNK, TGFb and p53 pathways (Zhang et al, 1999(Zhang et al, , 2000Furuhashi et al, 2001;Rui et al, 2004).…”
mentioning
confidence: 99%